2011
DOI: 10.3892/ijo.2011.1145
|View full text |Cite
|
Sign up to set email alerts
|

A murine model of hepatitis B-associated hepatocellular carcinoma generated by adeno-associated virus-mediated gene delivery

Abstract: Abstract.A relevant animal model is critical for investigating the pathogenic mechanisms underlying hepatitis B virus (HBV)-induced hepatocellular carcinoma (HCC). Mice are not naturally infected by HBV, presumably due to the lack of HBV receptors on mouse hepatocytes. To bypass this entry step of HBV infection, we report generation of a novel HBV model in immunocompetent mice by hepatic delivery of the HBV genome using trans-splicing adeno-associated viral vectors (AAV/HBV). We confirmed production of HBV vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In addition, 100% of these mice (12 out of 12) developed visible tumor nodules in the liver within 16 weeks. 26 We did not observe any tumor formation in 33 HBV-infected mice that had been monitored for more than 1 year, although we used the same HBV strain (a genotype D virus). In our study, one AAV construct containing the entire HBV genome was used, whereas Tao et al .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, 100% of these mice (12 out of 12) developed visible tumor nodules in the liver within 16 weeks. 26 We did not observe any tumor formation in 33 HBV-infected mice that had been monitored for more than 1 year, although we used the same HBV strain (a genotype D virus). In our study, one AAV construct containing the entire HBV genome was used, whereas Tao et al .…”
Section: Discussionmentioning
confidence: 90%
“…In our study, one AAV construct containing the entire HBV genome was used, whereas Tao et al . 27 used two AAVs each containing one half of the HBV genome. However, whether this difference in AAV constructs contributes to liver cancer formation remains to be determined in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of miR-15b down-regulation on HBV was observed in a persistent HBV expression mouse model: rAAV8–1.3HBV infected-mouse (22,23). We first evaluated the efficiency of pCAGGs-15b transduction after hydrodynamic injection and found that pCAGGs-15b was able to effectively inhibit in vivo expression of endogenous miR-15b, while it promoted in vivo expression of HNF1α, the target of miR-15b (Supplementary Figure S2A and S2B).…”
Section: Resultsmentioning
confidence: 99%
“…rAAV8–1.3HBV-transduced mouse model: HBV persistent replication with recombinant Adeno-Associated Virus 8 (AAV, serotype 8) carrying 1.3 copies of HBV genome (rAAV8–1.3HBV) was induced by tail vein injection of rAAV8–1.3HBV (1 × 10 11 vg/200 μl/mouse) (22,23). …”
Section: Methodsmentioning
confidence: 99%
“…Many researchers have established HBV replication models in immunocompetent nontransgenic mice by employing hydrodynamic injection [36] or adenoviral vector delivery [37], [38], but in most cases only acute hepatitis can be demonstrated, and the HBV infection is eventually cleared. Persistent HBV replication in a mouse model has been demonstrated only under special conditions in which the HBV DNA was cloned in an adeno-associated viral (AAV) vector and then delivered to mouse livers either via hydrodynamic injection [39] or via AAV infection [40]. The mechanism for this persistence is partly dependent on the AAV vector, which has been shown to be poorly detected by host innate immunity and favors long-term persistence in the cells [41], [42].…”
Section: Discussionmentioning
confidence: 99%